ส่วนประสมการตลาดที่มีผลต่อผู้บริโภคในอำเภอเมืองเชียงใหม่ต่อการซื้อสบู่สมุนไพร - สิริกร ศิริอางค์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This independent study aimed to examine marketing mix affecting consumers in Mueang Chiang Mai district towards buying herbal soaps. Data were collected by the distribution of 300 questionnaires to male and female consumers of herbal soaps who resided or worked in Mueang district, Chiang Mai. Data acquired were then analyzed by the use of descriptive statistic consisting of frequency, percentage, and mean. According to the study, the majority of respondents in the age between 20-29 years old worked as company employee. They were studying or hold the Bachelor’s degree and earned the average monthly income at 5,001-15,000 Baht. The respondents paid high level of importance to the marketing mix factors affecting consumers towards buying herbal soaps as follows: product, promotion, price and place, respectively. In product factor, the top three important sub-factors were to be non-allergenic product, to indicate benefit of product explicitly and the list of ingredients advised, in orderly. In price factor, the top three important sub-factors were the reasonable price to product quality and quantity and the price tag vividly shown at the selling point, in orderly. In place factor, the top three important sub-factors were the convenience to buy products, the product distribution at supermarkets and the availability of product in-stocks at all times, in orderly. In promotion factor, the top three important sub-factors were to have brochures introducing products and advantages of herbs, to have service-minded and polite product consultant who had good knowledge on products at the selling point and to distribute free sample products to consumers, in orderly.